ПРАЗДНИКИ КАК ФОРМА ДУХОВНОГО ОБОГАЩЕНИЯ УЧАЩИХСЯ - Кравченко, Т.Н. (My University, 2019)
Аннотация В статье описывается опыт использования информации о необычных праздниках как приема внешней интеграции нравственно-духовного образования «Самопознание». Abstract The article describes the experience of using information about unusual holidays as a method of external integration of moral and spiritual education «Self-knowledge».
Holidays as a form of spiritual enrichment of students
Keywords: внешняя интеграция нравственно-духовного образования «Самопознание»; праздники; практический опыт.; external integration of moral and spiritual education «Self-knowledge»; holidays; practical experience